Influence of Halide Substitution on Local and Average Structure, Lattice Dynamics, and Transport Properties in Cu6PS5X Argyrodites - Anupama Ghata; Bibek Samanta; Thorben Böger; Xabier Martinez de Irujo-Labalde; Emmanuelle Suard; Matthias T. Agne; Michael Ryan Hansen; Wolfgang G. Zeier (Journal of the American Chemical Society, 2026)
Abstract Halide-substituted argyrodite materials have attracted increasing attention for energy applications since compositional tuning provides an effective strategy to modulate their structure and transport characteristics. While Li+-based halide argyrodites have been extensively studied, a unified composition-resolved understanding of Cu+-based halide argyrodites that integrates phase evolution, local structure, lattice dynamics, and electronic and ionic transport remain limited. In this work, we investigate Cu6PS5X (X = Cl, Br, I, Cl0.5Br0.5, Cl0.5I0.5, and Br0.5I0.5) within a combined experimental and computational framework. All compositions adopt an average cubic F4̅3m structure at room temperature, while local structural analysis reveals deviations from cubic symmetry consistent with a monoclinic Cc model involving PS43– tetrahedral tilting. 31P MAS NMR spectroscopy corroborates this local symmetry breaking through multiple distinct phosphorus environments arising from relative tetrahedral orientation rather than S2–/X– site disorder. Halide substitution modifies the Cu+ conductivity through changes in the activation energy and the Arrhenius pre-exponential factor, following the Meyer–Neldel behavior, with additional contributions from variations in jump distances and migration pathways. Direction-projected phonon density of states analysis identifies low-frequency Cu+ vibrational components along the crystallographic migration pathways. Analysis of the Meyer–Neldel slope further suggests phonon assisted ion hopping involving multiphonon excitation of low-frequency Cu+ vibrational modes. Together, these findings offer insight into structure–property relationships in Cu6PS5X and suggest that, alongside the migration energy landscape, the vibrational energy scale, thermal population, and directionality of mobile ion modes should be considered when interpreting ion transport, thereby providing a vibrational perspective for the design of solid-state ion conductors.